تاريخ الفكر الفلسفي بين هيجل و هايدغر - بركات غسان (Tishreen University Journal- Arts and Humanities Sciences Series, 2018)
تكمن أهمية هذا البحث في كونه من البحوث ذات الدلالة المعرفية والفلسفية الهامة، فالتاريخ ليس متعاقباً لعصور وإنما هو اقتران لذات الشيء الذي يعني الفكر في أنماط متعددة وفي صيغ متنوعة. فتاريخ الفلسفة لا يتنافر مع الفلسفة بل ينطبق معها؛ في فكر هيجل وتاريخ الفلسفة هو هذا التعاقب والتطور في الزمان. والبحث يشير إلى الفرق بين هايدغر و هيجل في إدراك كل منهما لحركة التاريخ وعلاقة تلك الحركة بأصولها. وإن هيجل يؤكد على أننا في تاريخ الفلسفة لا نكون أمام ماض بالرغم من أننا نكون أمام تاريخ. إذ إنّ محتوى ذلك التاريخ يتكون من المنتوجات العلمية للعقل. أما علاقة الفكر بالوجود عند هايدغر فهي علاقة ذات بموضوع، بينما لدى هيجل فهي كذلك لأن المنطق لدى هيجل ليس قواعد صورية وإنما ما يقوله الوجود. The importance of this research as a significant body of research knowledge and philosophical history is important not punish for ages, but is coupled to the same thing, which means thinking in multiple styles in a variety of formats. The history of philosophy is not incompatible with the philosophy but applies them in the thought of Hegel and the history of philosophy is this sequence and evolution in time. Research refers to the difference between Heidegger and Hegel to recognize each of the movement of history and the relationship of that movement origins. If Hegel emphasizes that we are in the history of philosophy is not to be past, although we be in front of a date. As the content of that history consists of products of the scientific mind. Relationship is not thought to exist when the relationship with the subject of Heidegger, Hegel, while when there is between the self and the subject as there is between the image and content between existence and meaning.